Yellowstone Through the Ages - Howard, Arthur D. (Columbia University Press, 1938)
Presents the events of the history of Yellowstone National Park which have brought about its beautiful canyons, waterfalls, lakes, hot springs, geysers, and accumulations of volcanic materials
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: SCIENCE / Earth Sciences / Geology